Carbonyl Allylation and Crotylation: Historical Perspective, Relevance to Polyketide Synthesis, and Evolution of Enantioselective Ruthenium-Catalyzed Hydrogen Auto-Transfer Processes - Ortiz, Eliezer; Saludares, Connor; Wu, Jessica; Cho, Yoon; Santana, Catherine G.; Krische, Michael J. (Synthesis, 2023)
The evolution of methods for carbonyl allylation and crotylation of alcohol proelectrophiles culminating in the design of iodide-bound ruthenium-JOSIPHOS catalysts is prefaced by a brief historical perspective on asymmetric carbonyl allylation and its relevance to polyketide construction. Using gaseous allene or butadiene as precursors to allyl- or crotylruthenium nucleophiles, respectively, new capabilities for carbonyl allylation and crotylation have been unlocked, including stereo- and site-selective methods for the allylation and crotylation of 1,3-diols and related polyols.1 Introduction and Historical Perspective2 Ruthenium-Catalyzed Conversion of Lower Alcohols into Higher Alcohols3 Conclusion and Future Outlook
Keywords: polyketide; ruthenium; feedstock; allene; butadiene; allylation